Structural, functional, and evolutionary analysis of late embryogenesis abundant proteins (LEA) in Triticum aestivum: A detailed molecular level biochemistry using in silico approach. (October 2019) - Bhattacharya, Shreya; Dhar, Shreyeshi; Banerjee, Arundhati; Ray, Sujay
Graphical abstract: Highlights: Analysis of conserved LEA domains in Triticum aestivum in 6 LEApdB classes. Assignment of LEApdB class 4 to unclassified WZY2-1 protein. Analysis of the LEA4 domain from Class 6 lea proteins . Functional diversity in Class 6 lea proteins for 310 →helix-turn shift. Analysis of the functional change in Class 6 lea proteins for 310 -helix→turn shift. Analysis of evolutionary relationship between Triticum aestivum and Aegilops. Abstract: LEA (Late Embryogenesis Abundant) proteins are abundant in plants and play a crucial role in abiotic stress tolerance. In our work, we primarily focused on the variations in physiochemical properties, conserved domains, secondary structure, gene ontology and evolutionary relationships among 40 LEA proteins of Triticum aestivum (common wheat). Wheat LEA protein belongs to first 6 classes out of the 13 classes present in LEApdB, the comprehensive database for LEA proteins. Proteins belonging to each LEApdB class have structures and functions distinguished from other classes. The study found three different conserved LEA domains in Triticum aestivum. One important domain was dehydrin, present in wheat proteins of classes 1, 2 and 4, though varied in sequence level, have similar biological processes. The study also found sequence level and phylogenetic similarity between dehydrin domains of class 1 and 4, but distinct from that of LEApdB class 2. This study also demonstrated functional diversity in two class 6 proteins occurred due to many destabilizing mutations in the LEA4 domain that caused alteration of ligand binding and conformational shift from 310 -helix → turn within the domain. The LEA4 domains of these proteins also showed functional similarity and evolutionary relatedness with three other proteins of genus Aegilops, denoting that these proteins in Triticum aestivum were derived from its ancestor Aegilops. The study also assigned LEApdB class 4 to an unclassified LEA protein 'WZY2-1' based on amino acid composition, conserved domain, motif architecture and phylogenetic relatedness with class 4 proteins. Our study has revealed a detailed analysis of LEA proteins in Triticum aestivum and can serve as a pillar for further investigations and comparative analysis of wheat LEA proteins with other cereal or plant types.